Dinamika Psikologis pada Mahasiswa Perokok yang Relapse di UIN Antasari Banjarmasin - Nida, Khairun; Hairina, Yulia; Imadduddin, Imadduddin (Jurnal Al-Husna, 2022)
Students are individuals who study in universities. In the education structure in Indonesia, students hold the highest educational status. Based on initial observations at the UIN Antasari Banjarmasin campus, many students have become active smokers. Smoking behavior is sometimes without regard to the people around them, even though smoking activities often have a negative impact on both the people around and the individual smokers themselves. Of the students who actively smoke, some of them have experienced a relapse phase, the reoccurrence of the old pattern, namely a condition that has recovered from an activity (smoking), repeats the activity for various reasons. The type of research used is field research (field research) with a descriptive qualitative approach. The subject is a smoker student who relapses at UIN Antasari Banjarmasin. Data collection techniques using interview and observation techniques. The data analysis technique uses data reduction, data presentation, and conclusion drawing. The results of the study obtained psychological dynamics and the causes of relapse for student smokers.